Growth performance, intestinal health, and non-specific immunity were significantly affected by feeding different compound lactic acid bacteria supplementation in sea urchin (Strongylocentrotus intermedius) - Yuntian Zhang; Yuntian Zhang; Rongwei Zhang; Rongwei Zhang; Yi Chen; Yi Chen; Zhixu Guo; Zhixu Guo; Xiangyu Meng; Xiangyu Meng; Yuzhe Han; Yuzhe Han; et al. (Frontiers in Marine Science)
A 50-day feeding trial was conducted to evaluate the effects of dietary supplementation with different levels of compound lactic acid bacteria on the growth performance, antioxidant capacity, intestinal microbiota composition, and immunity of the Strongylocentrotus intermedius. In this study, S. intermedius with an initial body weight of 26.47 ± 0.27 g was used as the experimental subject. Based on dietary supplementation with compound lactic acid bacteria (containing 56.15% Lentilactobacillus and 20.59% Acetobacter) at different levels, the subjects were categorized into four experimental groups: 0% (RC), 0.5% (RL), 1% (RM), and 2% (RH). The dietary supplementation with compound lactic acid bacteria significantly improved the growth performance of S. intermedius in the RL, RM, and RH groups, including final body weight (FBW), weight gain rate (WGR), specific growth rate (SGR), and gonadosomatic index (GSI). Furthermore, antioxidant and immune indicators such as total antioxidant capacity (T-AOC), superoxide dismutase (SOD), catalase (CAT), acid phosphatase (ACP), alkaline phosphatase (AKP), and lysozyme (LZM) were significantly enhanced. Notably, compound lactic acid bacteria improved digestive enzyme activities in the intestine and reduced the feed conversion ratio (FCR). Supplementation with compound lactic acid bacteria reduced Arcobacter and Vibrio colonization in the intestinal tract and enhanced the expression of genes related to antioxidant, stress, and immune responses in the RM and RH groups. Overall, 1% compound lactic acid bacteria supplementation in the diet significantly improved growth performance, digestive capacity, non-specific immune ability, and intestinal microbial stability in S. intermedius.